A SOCIO-FACTOR ANALYSIS OF COMMUTE TRANSITION: THE MOBILE POPULATION OF CAPITAL REGION INDIA - Dr. Anand Kumar Gupta (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Today, workforce well being is critical for economic success of any nation. This research paper is an attempt to define commuting as everyday travel between home and work independent of mode, distance and time. Literature is used to establish expert consensus on commute well being requirements and strategies were rated over literature outcome to generate positive mental health and well-being in the workplace commute. Commuting is the regular trip between home and work. Travelers utilize different means of move such as lashing personal car, general buses and rail transportation. Analyses depict that time taken for travel to office and back home has significant impact on employee behavior. The cost of commute may understand in the form of travel fatigue experience and distance of daily commute. The final outcome of this research work derived as job dissatisfaction of employee. All the analyses, findings and suggestions have been enumerated in the conclusion. Future prospects and commute related factors have a significant effect on commuter job satisfaction. The current task brings clarity and makes more concrete the evidence of procedure and mental process involved in the experience of mobbing and its linked outcome in the context of India. The present study is an investigation of commuters well being as moving labor market in India as the Indian railway transport system under the operational circumstances which leads serious problems to the commuter as stress and feeling of exertion which reflect in the form of job satisfaction.